Analysis and establishment of adult diagnostic reference level for whole-body 18F-FDG PET/CT imaging: A single institutional study - Ahmad Faez, Mohamed Ridhwan; Chen, Ew-Jun *; Haniff Shazwan, Safwan Selvam; Chew, Ming Tsuey * (Elsevier, 2023)
Whole-body fluorine-18-fluoro-2-deoxy-D-glucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) has been mostly recognized for managing oncologic patients. However, there is a growing concern over the radiation exposure of patient undergoing PET/CT due to higher radiation dose compared to other imaging modalities. Diagnostic reference level (DRL) can be used as a tool to optimize the use of radiological imaging procedure in a way that suits the health needs and reduce radiation exposure while maintaining image quality. The aim of this study is to establish a local DRL received by adult patients that undergone a whole-body 18F-FDG PET/CT at Sunway Medical Centre. Dose data such as activity, EDPET, CTDIvol, DLP, EDCT and EDcumulated were retrospectively collected for 300 patients each for both PET/CT uMI 780 (System I) and PET/CT Biograph mCT 20 Excel (System II). The 75th percentile of dose distribution were calculated and compared with other established DRLs. DRL for EDPET, CTDIvol, DLP, EDCT and EDcumulated for System I were 175.96 MBq, 3.34 mSv, 1.86 mGy, 1854.34 mGy cm, 27.76 mSv and 31.13 mSv while for System II were 212.35 MBq, 4.03 mSv, 12.48 mGy, 1198 mGy cm, 17.55 mSv and 21.83 mSv, respectively. There is signifant difference for both PET and CT dose value between PET/CT (p-value <0.05). Our DRL showed that the 18F-FDG activity dose was the lowest while the CTDIvol and DLP were the highest among the other established DRLs. The local DRL for whole-body 18F-FDG PET/CT is established.